Exploring Corporate Level Strategy Customer Relationship Management - Muhamad Fairos b Mohamad Shah; Md Sadikul Hasan Khan (Istithmar, 2024)
Corporate label strategy sets a company's long-term aims. Strategic decisions must incorporate market movement, competition, resource allocation, and diversity. This abstract introduces the corporate-level strategy, its importance, and major parts. Top management's decisions and actions set the corporate strategy. Mission statements must state the company's long-term goals and beliefs. In order to maximize shareholder value, corporate-level strategy aims to improve company performance and competitiveness. A frequent first step in developing a corporate strategy is defining the scope of an organization's operations. For this, the company must choose its markets, clients, and marketplaces.  Market dynamics, growth potential, and competitive advantages influence these decisions. In order to increase operations and acquire a competitive edge, businesses may diversify their product offerings, integrate their supply chains, or expand into new geographies.